FoxP3 in Treg cell biology: a molecular and structural perspective. (3rd September 2019) - Deng, G; Song, X; Greene, M I
Summary: Regulatory T cells (Tregs ) are specialized in immune suppression and play a dominant role in peripheral immune tolerance. Treg cell lineage development and function maintenance is determined by the forkhead box protein 3 (FoxP3) transcriptional factor, whose activity is fine-tuned by its post-translational modifications (PTMs) and interaction partners. In this review, we summarize current studies in the crystal structures, the PTMs and interaction partners of FoxP3 protein, and discuss how these insights may provide a roadmap for new approaches to modulate Treg suppression, and new therapies to enhance immune tolerance in autoimmune diseases. Graphical Abstract: